Impact of Central Event Adjudication on the PLATO Trial Results - Victor L. Serebruany; Wendy Ziai; Hector A. Cabrera-Fuentes; Brendon Pokov; Isabella Hwang; Thomas Marciniak (Reviews in Cardiovascular Medicine)
Background: This study aimed to determine the impact of central adjudication of site-reported events in patients with acute coronary syndromes treated with ticagrelor or clopidogrel in addition to aspirin within the frame of indication-seeking The PLATelet Inhibition and Clinical Outcomes (PLATO) trial. Adjudication in randomized outcome-driven trials is supposed to maintain integrity by applying uniform rules for the quality assessment of clinical events. Some preliminary data suggest an imbalance between central and site diagnoses in PLATO. We gained access to the Food and Drug Administration (FDA)-issued adjudication dataset and analyzed the evidence. Methods: Death, myocardial infarction (MI), stroke/ transient ischemic attack (TIA), bleeding, arterial thrombotic events, and cardiac ischemic events underwent central adjudication. We assessed geography, timing, impact of disagreements, and primary endpoint composition. Results: Among 18,624 trial enrollees, 10,704 central adjudications occurred across 7171 patients in 43 countries. There were 938 deaths, 2751 cases of MI, 359 strokes/TIAs, 2680 cardiac events, 130 thrombotic events, and 3782 bleeding events. The match occurred for 5451 events, while mismatches favoring clopidogrel (n = 2535) or ticagrelor (n = 2706) (p = 0.79) were common for major (n = 1797), moderate (n = 942), or minor (n = 735) disagreements. The central decision prevailed in 2945 cases. There was a significant (HR = 0.84; 95% confidence intervals (CI): 0.75–0.95; p = 0.004) adjudication delay in the 2007–2008 events but finalized in 2009. Ticagrelor was significantly less favored in 2009 than in 2007–2008 (HR = 1.19; 95% CI: 1.05–1.34; p = 0.005). There was a remarkably consistent match for bleeding adjudication (HR = 1.02; 95% CI: 0.83–1.25; p = 0.859) between treatment arms. The primary endpoint in the PLATO trial exhibited highly significant disagreement favoring ticagrelor for vascular death (HR = 2.02; 95% CI: 1.1–3.64; p = 0.019); MI (HR = 2.31; 95% CI: 2.79–43.94; p = 0.034); stroke (HR = 1.37; 95% CI: 2.66–63.28; p = 0.036); total events (HR = 2.51; 95% CI: 1.86–3.39; p = 0.01). Conclusion: Central adjudication in the PLATO trial was delayed and impacted the primary endpoint by inflating the ticagrelor benefit, resulting in drug approval. The regulatory authorities should consider independent audits when unblinding is suspected in the indication-seeking clinical trials.